The yearning for freedoom in Hannah Arendt’s work - Losada Sanz, Milagros (Differenz. Revista internacional de estudios heideggerianos y sus derivas contemporáneas, 2022)
The idea of freedom in Arendt’s work exceeds the experience that one has ever had of it. Clung on to a rich anthropological approach, this idea does not lose its political nature to become nourishment for the hope by honoring the essence of the concept itself; without turning down the always alert criticism against all that may endanger the valuable potential that humans possess: the ability to be free.